Meta-analysis of serological biomarkers at hospital admission for the likelihood of developing delirium during hospitalization - Bassi, Thiago; Rohrs, Elizabeth; Nicholas, Michelle; Reynolds, Steven (Frontiers in Neurology, 2023)
Importance: Identifying biomarkers that, at hospital admission, predict subsequent delirium will help to focus our clinical efforts on prevention and management. Objective: Investigate biomarkers at hospital admission that may be associated with delirium during hospitalization. Data Sources:A librarian at the Fraser Health Authority Health Sciences Library performed searches from June 28th, 2021, to July 9th, 2021, using the following sources: Medline, EMBASE, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, Cochrane Methodology Register, and the Database of Abstracts of Reviews and Effects. Study Selection: The inclusion criteria were articles in English that investigated links between serum concentration of biomarkers at hospital admission and delirium during hospitalization. Exclusion criteria were single case reports, case series, comments, editorials, letters to the editor, articles that were clearly not relevant to the review objective, and articles concerning pediatrics. After excluding duplicates, fifty-five studies were included. Data Extraction and Synthesis:This meta-analysis followed the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) protocol. Independent extraction, with the consensus of multiple reviewers, was used to determine the final studies included. The weight and heterogeneity of the manuscripts were calculated using inverse covariance with a random-effects model. Main Outcome(s) and Measure(s): Differences in mean serum concentration of biomarkers at hospital admission between patients who did and did not develop delirium during hospitalization. Results:Our search found evidence that patients who developed delirium during hospitalization had, at hospital admission, significantly greater concentrations of certain inflammatory biomarkers and one blood-brain barrier leakage marker than patients who did not develop delirium during hospitalization (differences in the means: cortisol: 3.36 ng/ml, p<0.0001; CRP: 41.39 mg/L, p<0.00001; IL-6: 24.05 pg/ml, p<0.00001; S1000.07 ng/ml, p<0.00001). These differences were independent of other confounding variables such as patient’s severity of illness. A significantly lower serum concentration, at hospital admission, of acetylcholinesterase (difference in the means −0.86 U/ml, p=0.004) was also associated with an increased vulnerability to developing delirium during hospitalization. Conclusions:Our meta-analysis supports the hypothesis that patients with hypothalamic-pituitary axis dysfunction, increased blood-brain barrier permeability, and chronic overload of the cholinergic system, at hospital admission, are more vulnerable to developing delirium during hospitalization.